Sustainable Agriculture Education and Civic Engagement: The Significance of Community-University Partnerships in the New Agricultural Paradigm - Kim L. Niewolny; Julie M. Grossman; Carmen J. Byker; Jennifer L. Helms; Susan F. Clark; Julie A. Cotton; Krista L. Jacobsen (Journal of Agriculture, Food Systems, and Community Development, 2016)
Universities and colleges across the United States are making innovative strides in higher education programming to catalyze a more sustainable era of agriculture. This is clearly exemplified through the formation of community-university partnerships as critical illustrations of civic engagement (CE) for sustainable agriculture (SA) education. This paper explores the praxis of CE for SA education by focusing on the ways in which five land-grant universities (LGUs) with undergraduate programs in SA have developed and put into practice community-university partnerships. Drawing upon these programs and supportive literature, this article specifically attempts to describe the role and significance of CE for SA education, emerging community-university partnership models and their implications for prompting food and agriculture sustainability, and student learning and program assessment outcomes. We also reveal the many challenges and opportunities encountered by stakeholders involved in the creation and continuation of these programs and their subsequent coursework. Conclusions offer "real world" recommendations for other faculty, staff, student, and community stakeholders to implement and generate action-oriented scholarship for and with communities as a viable thread of SA education.